Dentin bond strength of an adhesive system irradiated with an Nd:YAG laser. (30th September 2016) - Ruschel, V C; Malta, D A M P; Monteiro, S
Abstract: The objective of this study was to evaluate the microtensile bond strength of an adhesive system applied to dentin, followed by Nd:YAG laser irradiation. Twenty-two recently extracted third molars were divided into four groups ( n = 5). In the G1 and G2 groups, the adhesive system was applied conventionally, and in groups G3 and G4, the adhesive system was irradiated with an Nd:YAG laser (100 J cm −2 ). The specimens were stored in distilled water at 37 °C, those in groups G1 and G3 for 24 h, and those in groups G2 and G4 for 3 months. Two teeth from groups G1 and G3 were used for observation of the hybrid layer, using a confocal microscope ( n = 1). The teeth were submitted to a microtensile bond strength test. Analysis of the type of fracture was performed using a stereoscope (40×). The results for microtensile bond strength (MPa) and standard deviation (±SD) were: G1—31.68 (5.14); G2—37.88 (±5.04); G3—35.32 (±8.79); G4—31.53 (±9.01). There were no significant differences among the groups ( p > 0.05). Adhesive failure was predominant in all the groups. The Nd:YAG laser irradiation of the adhesives did not influence dentin bond strength during the periods of 24 h or 3 months of storage in distilled water.